Bacterial biofilms with emphasis on coagulase-Negative staphylococci - Oliveira, A. [UNESP]; Cunha, M. L.R.S. [UNESP] (FapUNIFESP (SciELO), 2008)
In addition to their capacity to attach to surfaces, various groups of microorganisms also produce an extracellular polymeric substance known as slime. This slime forms a thin layer around cells known as biofilm. Thus, biofilm structure comprises bacterial cells and an extracellular polymeric substance. It also presents a defined architecture, providing the microorganisms with an excellent protective environment and favoring the exchange of genetic material between cells as well as intercellular communication. The ability to produce biofilm is observed in a large group of bacteria, including coagulase-negative staphylococci (CNS) which are the predominant microorganisms of normal skin flora and have been implicated as the causative agents of hospital infections. Bacteremia caused by these agents is common in immunodepressed persons, in patients with cancer, in adult and neonatal intensive care units (ICU) and in patients using catheters or other prosthetic devices. The pathogenicity of CNS infections is probably related to the production of slime, which adheres preferentially to plastic and smooth surfaces, forming a biofilm that protects against attacks from the immune system and against antibiotic treatment, a fact hindering the eradication of these infections. The main objective of the present review was to describe basic and genetic aspects of biofilm formation and methods for its detection, with emphasis on biofilm creation by CNS and its relationship with diseases caused by these microorganisms which are becoming increasingly more frequent in the hospital environment.
Keywords: Biofilm; Coagulase-negative staphylococci; Infection; Microbiology; Slime